2021
DOI: 10.30880/ijscet.2021.12.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Factors Influencing Time and Cost Risks in Highway Construction Projects

Abstract: The construction of highway projects involves many types of risks throughout the various stages of itsproject life cycle. Those risks are especially significant due to their impact on the project performance and objectives, mainly in terms of costs and time. Several factors of projects risk had been determined and well explained in the paper. Major risks involved in highway construction in Malaysia are cost risk, safety risk and time risk. Due to lack of opinion from the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Lack of knowledge on project planning and on the impact that this deficiency exerts on the construction delays in Vietnam is an established challenge affecting the client party [31,[115][116][117]. This study identified a routinely emergent, prominent issue, namely site safety; the existing literature noted that these issues lead to conflicts among project stakeholders and negatively affect construction project performance [110,118,119]. Previous studies also observed that safety issues often emerge due to poor knowledge on safe construction methods and behavioral shortcomings, and that a lack of awareness among workers often leads to injuries and further impacts project performance [21,116,119].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of knowledge on project planning and on the impact that this deficiency exerts on the construction delays in Vietnam is an established challenge affecting the client party [31,[115][116][117]. This study identified a routinely emergent, prominent issue, namely site safety; the existing literature noted that these issues lead to conflicts among project stakeholders and negatively affect construction project performance [110,118,119]. Previous studies also observed that safety issues often emerge due to poor knowledge on safe construction methods and behavioral shortcomings, and that a lack of awareness among workers often leads to injuries and further impacts project performance [21,116,119].…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors are associated with building projects. These risks manifest in various phases of the projects life cycle commencing from the feasibility stage through completion, handing over and maintenance (Bakri et al, 2021). Further, in recent years of active construction of building projects, the scope of work, the timing and limited finance paved way for the emergence of risks influencing the budget and project's duration (Lapidus et al, 2022b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, construction risks and financial risks are the most frequently occurring while servicing relocation, design changes, additional works, and price fluctuation influence cost risks in the Malaysian construction industry. Similarly, the main factors influencing the schedule of the project are permit approval, the condition of the weather, reduced workers' productivity, untimely preparation and approval of drawings, changes to the design, and worker shortage (Bakri et al, 2021). Moreover, the construction industry is plagued by risks thereby subjecting it to an age-long poor track record in comparison with other economy sectors (Mishra & Mishra, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations